Cervista HPV assays for fine‐needle aspiration specimens are a valid option for human papillomavirus testing in patients with oropharyngeal carcinoma. Issue 2 (11th December 2013) - Guo, Ming; Khanna, Abha; Dhillon, Jasreman; Patel, Shobha J.; Feng, Jie; Williams, Michelle D.; Bell, Diana M.; Gong, Yun; Katz, Ruth L.; Sturgis, Erich M.; Staerkel, Gregg A.
Abstract : BACKGROUND: The objectives of this study were to evaluate the validity of Cervista human papillomavirus (HPV) assays in head and neck fine‐needle aspiration (FNA) specimens from patients with head and neck squamous carcinomas and to verify that the Cervista assay in FNA specimens is a valid option for determining HPV status in patients with oropharyngeal carcinomas. METHODS: The authors retrospectively retrieved 64 head and neck FNA specimens from patients who had head and neck squamous carcinoma. The specimens were tested for HPV types 16 and 18 (HPV16/18) and for high‐risk (HR) HPV DNA using the Cervista HPV16/18 and HPV HR assays, respectively. The results from those assays were compared with the results from polymerase chain reaction (PCR)‐based HPV assays in the same tissues and with the results from HPV in situ hybridization assays/p16 immunostaining in the corresponding primary tumors. RESULTS: In total, 64 FNA specimens were analyzed. The Cervista HPV16/18 and/or HPV HR assays were positive in 48 of 64 specimens (75%), and there was a predominance of HPV16 (42 of 48 specimens; 88%). In the 49 specimens that had PCR‐based test results, overall agreement with Cervista assay results was 96% (47 of 49 specimens; κ = 0.883). In the 49 specimens that had PCR‐based HPV16/18 genotyping results, overall agreement with the Cervista HPV16/18 results was 94% (46 of 49 specimens; κ = 0.847). In the 36 primary carcinoma specimens that had valid HPV in situ hybridization/p16 immunostaining results, overall agreement with the Cervista assay results was 92% (33 of 36 specimens; κ = 0.679). CONCLUSIONS: Cervista HPV16/18 and Cervista HPV HR testing of head and neck FNA specimens is a valid option for determining HPV16/18 status in patients with oropharyngeal carcinoma. Cancer (Cancer Cytopathol) 2014;122:96–103 . © 2013 American Cancer Society . Abstract : Sixty‐four fine‐needle aspiration (FNA) specimens from patients with head and neck squamous carcinoma are tested using the Cervista human papillomavirus type 16/18 (HPV16/18) assay and the Cervista HPV HR assay (for high‐risk HPV types), and the results are compared with polymerase chain reaction‐based HPV results from the same tissues and with HPV in situ hybridization assay/p16 immunostaining results from the corresponding primary tumors. The findings indicate that use of the Cervista HPV assays for testing head and neck FNA specimens is a valid option for determining HPV16/18 status in patients with oropharyngeal carcinoma.